KEPEMIMPINAN KEPALA MADRASAH DALAM MENINGKAKTAN PROFESIONAL GURU DI MA MA’HAD ALI BIN ABI THALIB - Abdul Halim; Sugiran; Nur Widiastuti (UNISAN JURNAL, 2025)
This study aims to determine the leadership of the principal in improving teacher professionalism at MA Ma’had Ali Bin Abi Thalib. The data sources in this study were the principal and all teachers. Data collection tools in this study were observation, interviews and documentation. This study used a qualitative approach with a descriptive qualitative nature. The results of this study are the leadership of the principal in improving teacher professionalism, various strategies and methods are used, one of which is providing rewards for teachers who have achievements, providing sanctions for teachers who violate the rules set by educational institutions, being firm, wise and responsible.